Individual determinants of extended working lives: A systematic review of the literature - Rodolfo Gutiérrez; Fermín López-Rodríguez; Aroa Tejero (International Journal of Ageing and Later Life)
The extension of working lives (EWL) appears as a long-term transformation driven by the increase in longevity and the expansion of institutional incentives to postpone retirement. However, the increase in average retirement ages is being less intense and more heterogeneous than promised by pension reforms. The mismatch between structural and individual changes reinforces the interest of a precise knowledge of the influence of individual determinants on EWL. Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology (Page et al. 2021), this article provides a systematic review of literature with the objective of conceptualizing variants of EWL and systematizing empirical evidence of the influence of individual determinants on EWL. This review can be of benefit both for detecting the areas on which future research should focus and for guiding the discussions on potential pension system reforms while considering the heterogeneity of individuals’ profiles.